Mediastinal Germ Cell Tumors – A Clinicopathologic Study - Shamsuddin, Fatima; Khadilkar, Urmila N; Saha, Debarshi (Annals of Pathology and Laboratory Medicine, 2019)
Background: Primary mediastinal extragonadal germ cell tumors (GCT) are relatively rare lesions and account for only 1 to 2 percent of all germ cell tumors. They are clinically distinct from testicular germ cell tumors despite their similar histologic features. Objective of this study is to classify and evaluate the histomorphology of mediastinal germ cell tumors and correlate the clinical findings with radiological and other serologic parameters. Method: A 5 year study was done in Dept. of Pathology, of a private Medical College on mediastinal lesions. Total number of cases studied was 66, with GCTs making up 7 cases. Histopathology sections taken were stained with routine Hematoxylin and Eosin stains. Results: The age range of patients with mediastinal GCTs were 6 months to 43 years with a mean of 23 years. Only one case was seen above 40 years. Both malignant GCTs were below 20 years. There was a male predominance with male:female ratio of 2.5:1. Conclusion: Mediastinal GCTs are rare & interesting neoplasms, usually located in anterior compartment of mediastinum. A histomorphological analysis aided by radiology and serology permits an exact diagnosis in many cases.